Implementation of the Planning Information System (SinCan) in Improving the Assessment of Sub-district Performance Synergy (SKK) by the Bureau of Government and Regional Autonomy of East Java Province - Umi Sholihatu Marfu’atin; Vidya Imanuari Pertiwi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Planning Information System (SinCan) is a program used by the Bureau of Governance and Regional Autonomy to assess District Performance in East Java in an effort to realize data-based performance evaluation systematically and transparently. This research aims to determine the suitability of the implementation of the SinCan System program in the context of assessing District Performance Synergy (SKK) in East Java. The type of research used in this study is qualitative research with a descriptive approach. This research uses primary data through observation and interviews with the Head of the General Government Section as the provincial SKK assessment team, and the SinCan verifier team. The results of the research show that the implementation of SinCan is in accordance with the needs of the sub-district government in providing an effective, systematic, and transparent data-based evaluation tool. This program is also in line with the capacity of the implementing organization, namely the Bureau of Governance and Regional Autonomy, which already has adequate human resources and infrastructure to support SinCan implementation. In addition, there is a match between the program requirements and the capacity of the target group (sub-districts), although there are still challenges in understanding the data entry mechanism in the system. To overcome this obstacle, the researcher recommends regular training and technical assistance to sub-districts. Keywords:District Performance Synergy (SKK), Implementation, Performance Assessment, SinCan System.